1992
DOI: 10.1159/000227003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Estrogen Receptors on Routine Paraffin Sections of Breast Carcinomas: A Comparison with Frozen Sections and an Enzyme Immunoassay

Abstract: In this study the monoclonal antibody ER-ICA (HSpy222) to human estrogen receptor (ER) protein and the peroxidase-antiperoxidase method was used to detect the presence of ER in 83 cryostat sections and in 68 paraffin sections pretreated with pronase in a total of 86 primary breast cancers. In 72 out of the 86 studied cases, a comparative evaluation was performed between the semiquantitative ER-ICA method and the quantitative enzyme immunoassay ER-EIA. A good correlation was found between the semiquantitative E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…13, 16-21], There was a high heterogeneity in the expression and distribution of ER in the same case regarding percent ages of ER+ cells and intensity of immunostaining, a phenomenon already mentioned in cryostat sections [1,2, 4.6, 10-13, 15-20,22-27]. Additionally we found that the intensity of the immunostaining rose proportionaly to the percentage of F.R + cells, in a similar way to that described in breast carcinoma [13]. It seems that the staining in- Our finding on paraffin sections that the proliferative phase shows the higher mean numbers of ER + cells and the stronger staining intensity compared to the secretory phase, adenomatous hyperplasia and adenocarcinoma parallels the results reported by others on cryostat sections [1,2,4,6,10,11,28,29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…13, 16-21], There was a high heterogeneity in the expression and distribution of ER in the same case regarding percent ages of ER+ cells and intensity of immunostaining, a phenomenon already mentioned in cryostat sections [1,2, 4.6, 10-13, 15-20,22-27]. Additionally we found that the intensity of the immunostaining rose proportionaly to the percentage of F.R + cells, in a similar way to that described in breast carcinoma [13]. It seems that the staining in- Our finding on paraffin sections that the proliferative phase shows the higher mean numbers of ER + cells and the stronger staining intensity compared to the secretory phase, adenomatous hyperplasia and adenocarcinoma parallels the results reported by others on cryostat sections [1,2,4,6,10,11,28,29].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study the ER-ICA MAb is ap plied for the first time on routine endometrial paraffin sec tions after pretreatment with the enzyme pronase to raise the sensitivity of the monoclonal antibody H222 SPy com mercially available [12,13]. Our aim was to show that it is possible to demonstrate immunohistochemically the heterogenous expression ofER on paraffin sections simul taneously with the good preservation of morphological details allowing the comparative study of histopathological, diagnostic and prognostic features even in archival material of endometrial samples.…”
Section: Introductionmentioning
confidence: 99%